Causes of suppurative keratitis in Ghana. - Hagan, M (1995)
AIMS--Suppurative keratitis is a serious problem in all tropical countries, but very little information is available about the causative organisms in Africa. The objectives were to identify the causative organisms and the proportion of cases caused by fungi in southern Ghana, and to determine whether correct decisions about treatment could be made on the basis of Gram stain in the eye clinic. METHODS--Scrapings were taken from corneal ulcers of consecutive new patients presenting at Korle Bu Hospital, Accra, and inoculated on 'chocolate' and Sabouraud's agars. Further scrapings were taken for Gram staining and interpretation in the eye clinic. Duplicate slides were assessed by an experienced microbiologist in the UK. RESULTS--One or more organisms were cultured from 114 of 199 patients (57.3%), the most common being Fusarium species, Pseudomonas aeruginosa, and Staphylococcus epidermidis. Fungi, alone or in combination, were isolated from 56% of the patients who had positive cultures. In total, 122 patients (61.3%) had their treatment either determined or altered based on the results of the microbiological diagnosis; in 87 of these solely on the basis of direct microscopic examination. CONCLUSIONS--Infection by filamentous fungi accounted for more than half of the ulcers from which cultures were obtained. Both training in technique and experience in interpretation are necessary for microscopy based diagnosis by staff in the clinic to be of greatest value. Direct microscopy was particularly useful for detecting fungi.